(untitled) (INNOVATIVE ECONOMY, 2020)
Yasynska N.A. RESEARCH OF STRUCTURAL SHIFTS IN UKRAINIAN HOUSEHOLDS’ FINANCES Purpose. The aim of the article is the investigation of structural shifts in Ukrainian households’ finances using instruments of such dynamics as household incomes and expenditures and instruments of stock trading (Elliott Wave Theory and Fibonacci Ratio) to the existing incomes of the population of Ukraine. Methodology of research. General scientific and special methods are used in the process of research, in particular: the method of analysis of social and economic statistics of absolute and relative indicators of changes in structural shifts and structural differences of household finances is used to study the dynamics of structural changes in the portfolio of financial assets of households; for studying the curve of population’s incomes – the main principles of the wave theory of Elliot and the Fibonacci ratio are used. Findings. It is established that the economy and the financial system, which is capable of development, is not socially oriented economy or financial system at this stage of social and economic development. The negative characteristics of the current dynamics of structural shifts in households’ finances in Ukraine are revealed. Originality. Unlike the current monitoring of household incomes and expenditures, it is proposed to expand the social and economic statistics of absolute and relative indicators, which will enable them to explore their income and expense models depending on their respective social strata, and to publicly monitor the effectiveness of each formal norm in line with structural changes in within their portfolios of financial assets. The expediency of studying models of household income and expenditure depending on their belonging to the corresponding social stratum and calculation of the effectiveness of each formal norm according to structural changes in household income and expenditure is substantiated. Practical value. The results of the study can be used in the work of the financial management apparatus, in the implementation of the social function in the state, to create the preconditions for the intensification of financial activity of households in Ukraine. Key words: structure, income, expenses, household, financial asset, portfolio.